Sports law materials
ports Law encompasses many different areas of the law brought together in unique ways. Issues in traditional areas of the law such as antitrust, contracts, and torts are quite common. For further information in these areas see: Antitrust Contracts Torts Sports Law can be roughly divided into the areas of amateur, professional, and international sports. The distinction between a professional and amateur athlete is somewhat tenuous. So-called "amateur" student/athletes at universities often receive scholarships and other forms of compensation. Also, keep in mind that even though an athlete may be defined as an amateur by one organization, he may not be an amateur according to another. Of course, this leads to even more confusion. A simplistic, yet useful definition is that amateur athletes participate in sports as an avocation while professional athletes are involved in sports as a vocation.